High-Throughput Screening of a Functional Human CXCL12-CXCR4 Signaling Axis in a Genetically Modified S. cerevisiae: Discovery of a Novel Up-Regulator of CXCR4 Activity - Murphy, James W.; Rajasekaran, Deepa; Merkel, Janie; Skeens, Erin; Keeler, Camille; Hodsdon, Michael E.; Lisi, George P.; Lolis, Elias (Frontiers in molecular biosciences, 2020)
CXCL12 activates CXCR4 and is involved in embryogenesis, hematopoiesis, and angiogenesis. It has pathological roles in HIV-1, WHIM disease, cancer, and autoimmune diseases. An antagonist, AMD3100, is used for the release of CD34+ hematopoietic stem cells from the bone marrow for autologous transplantation for lymphoma or multiple myeloma patients. Adverse effects are tolerated due to its short-term treatment, but AMD3100 is cardiotoxic in clinical studies for HIV-1. In an effort to determine whether Saccharomyces cerevisiae expressing a functional human CXCR4 could be used as a platform for identifying a ligand from a library of less ∼1,000 compounds, a high-throughput screening was developed. We report that 2-carboxyphenyl phosphate (fosfosal) up-regulates CXCR4 activation only in the presence of CXCL12. This is the first identification of a compound that increases CXCR4 activity by any mechanism. We mapped the fosfosal binding site on CXCL12, described its mechanism of action, and studied its chemical components, salicylate and phosphate, to conclude that they synergize to achieve the functional effect.CXCL12 activates CXCR4 and is involved in embryogenesis, hematopoiesis, and angiogenesis. It has pathological roles in HIV-1, WHIM disease, cancer, and autoimmune diseases. An antagonist, AMD3100, is used for the release of CD34+ hematopoietic stem cells from the bone marrow for autologous transplantation for lymphoma or multiple myeloma patients. Adverse effects are tolerated due to its short-term treatment, but AMD3100 is cardiotoxic in clinical studies for HIV-1. In an effort to determine whether Saccharomyces cerevisiae expressing a functional human CXCR4 could be used as a platform for identifying a ligand from a library of less ∼1,000 compounds, a high-throughput screening was developed. We report that 2-carboxyphenyl phosphate (fosfosal) up-regulates CXCR4 activation only in the presence of CXCL12. This is the first identification of a compound that increases CXCR4 activity by any mechanism. We mapped the fosfosal binding site on CXCL12, described its mechanism of action, and studied its chemical components, salicylate and phosphate, to conclude that they synergize to achieve the functional effect.